Kandungan Unsur Hara Pada Pupuk Organik Tumbuhan Air Lokal: The nutrient content of organic fertilizers on local aquatic plants - Rosawanti, Pienyani (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2020)
Water hyacinth, giant salvinia and water lettuce are widely available in Central Kalimantan that can be used as organic fertilizer. This study aims to determine the nutrient content of solid and liquid organic fertilizers in water hyacinth, giant salvinia and water lettuce fertilizers. The results showed that solid organic fertilizer/compost and water hyacinth, water lettuce and giant salvinia liquid fertilizer have nutrient content needed by plants. In solid fertilizers, the Nitrogen of giant salviniacontent was 2.43% and lack of the minimum standard of solid organic fertilizer, while Phospor and Potassium content were not included in the standard. In liquid organic fertilizer, Nitrogen, Phospor and Potassium content were not included in the minimum standard organic fertilizer requirements